Front Cover. Issue 3 (5th February 2018) - Wang, Fang; McShea, William J.; Li, Sheng; Wang, Dajun
Abstract : The cover image, by Fang Wang et al ., is based on the Biodiversity Research Does one size fit all? A multispecies approach to regional landscape corridor planning, DOI:10.1111/ddi.12692 . Photo Credit: Fang Wang.